Association between altered proton magnetic resonance spectroscopy (1H MRS) findings and clinical symptoms of schizophrenia. - Ambros, Senair Alberto (2013)
Objective: To assess the metabolic alterations of the thalamus in subjects with schizophrenia compared to healthysubjects and to investigate whether specific schizophrenic symptoms are associated with metabolic alterationsmeasured by 1H MRS. Methods: This is a case-control study including patients with schizophrenia diagnosed usingthe Diagnostic and Statistical Manual of Mental Disorders - Fourth Edition, DMS-IV and the Operational CriteriaChecklist for Psychotic Illness (OPCRIT). Proton magnetic resonance spectroscopy (1H MRS) was used to assessmetabolite concentrations (N-acetylaspartate, choline, creatinine, myoionositol and lactacte) in the left and rightthalamus of 13 patients with schizophrenia and 13 healthy controls. Results: In this study, concentrations ofspecific metabolites in the thalamus, determined by 1H MRS, were similar for individuals with schizophrenia andcontrols. It was observed that cases with family history of schizophrenia and disorganized speech demonstrated areduction in the ratio of the metabolites NAA /Cho in the thalamic nuclei on the right side. However, those withorganized delusions, hallucinations and non-affective auditory hallucinations had an increase of metabolites on theright side compared to the left thalamus. Decreased thalamic metabolic activity in patients with positive symptomswas observed in contrast with those who had well-organized delusions and auditory non-affective hallucinations,core symptoms of schizophrenia. Conclusion: A lateralized thalamic involvement was verified, suggesting thatorganic and genetic factors compromise the right thalamus and that the disorganization associated with delusionsand hallucinations compromises the left thalamic nuclei. Further studies to investigate the correlation betweensymptoms and thalamic dysfunction are warranted. (Rev Neuropsiquiatr 2011;74:183-190)